Cardiovascular safety in refractory incontinent patients with overactive bladder receiving add‐on mirabegron therapy to solifenacin (BESIDE). Issue 5 (16th April 2017) - Drake, Marcus J.; MacDiarmid, Scott; Chapple, Christopher R.; Esen, Adil; Athanasiou, Stavros; Cambronero Santos, Javier; Mitcheson, David; Herschorn, Sender; Siddiqui, Emad; Huang, Moses; Stoelzel, Matthias
Summary : Aims/objectives: : In the BESIDE study, combination therapy (antimuscarinic [solifenacin] and β3 ‐adrenoceptor agonist [mirabegron]) improved efficacy over solifenacin monotherapy without exacerbating anticholinergic side effects in overactive bladder (OAB) patients; however, a potential synergistic effect on the cardiovascular (CV) system requires investigation. Methods: OAB patients remaining incontinent despite daily solifenacin 5 mg during 4‐week single‐blind run‐in, were randomised 1:1:1 to double‐blind daily combination (solifenacin 5 mg/mirabegron 25 mg, increasing to 50 mg after week 4), solifenacin 5 or 10 mg for 12 weeks. CV safety assessments included frequency of CV‐related treatment‐emergent adverse events (TEAEs), change from baseline in vital signs (systolic blood pressure [SBP], diastolic blood pressure [DBP], pulse rate) and electrocardiogram (ECG) parameters. Results: The frequency of hypertension, tachycardia and ECG QT prolongation, respectively, was low and comparable across combination (1.1%, 0.3%, 0.1%), solifenacin 5 mg (0.7%, 0.1%, 0.1%), and solifenacin 10 mg groups (0.8%, 0%, 0.1%). Adjusted mean (SE) change from baseline to end of treatment (EoT) in SBP, DBP, and pulse rate with combination (0.07 mm Hg [0.38], −0.35 mm Hg [0.26], 0.47 bpm [0.28]), solifenacin 5 mg (−0.93 mm Hg [0.38], −0.45 mm Hg [0.26], 0.43 bpm [0.28]) and solifenacin 10 mg (−1.28 mm Hg [0.38], −0.48 mm Hg [0.26], 0.27 bpm [0.28]) was generally comparable, with the exception of a mean treatment difference of 1 mm Hg in SBP between combination and solifenacin monotherapy; SBP was unchanged with combination and decreased with solifenacin monotherapy. Mean changes from baseline to EoT in ECG parameters were generally similar across treatment groups, except for QT interval corrected using Fridericia's formula, which was higher with solifenacin 10 mg (3.30 mseconds) vs. combination (0.49 mseconds) and solifenacin 5 mg (0.77 mseconds). Conclusion: The comparable frequency of CV‐related TEAEs, changes in vital signs and ECG parameters indicates no synergistic effect on CV safety outcomes when mirabegron and solifenacin are combined.